Specific detection of pigeon parvovirus with TaqMan real-time PCR technology - Cuiteng Chen; Chunhua Zhu; Shuyu Chen; Zhen Chen; Huanru Fu; YuYi Chen; Mengyan Zhang; Wenyu Zhang; Yu Huang; Longfei Cheng; Chunhe Wan (Poultry Science)
The viruses of the Parvoviridae family can infect both vertebrate and invertebrate animals. Recently, pigeon parvovirus (PiPV) was detected in the feces of wild urban pigeons. Owing to no specific detection platform for PiPV, studies on the epidemiology of PiPV are still a research gap. To achieve this goal, in this study, a TaqMan-based fluorescence quantitative PCR (TaqMan‒PCR) technique was established. The specific primers and probes used were designed on the basis of the NS gene characterization of PiPV downloaded from GenBank. After optimization, the established TaqMan‒PCR assay provides a sensitive, accurate, reliable and cost-effective platform for PiPV detection. We found that both YDPS and healthy birds can be found to have PiPV infection through field sample investigations, and we also investigated the presence of PiPV in Fujian, mainland China. Owing to the failure to propagate PiPV in embryos and cells, knowledge of PiPV replication mechanisms in birds still needs further study. In conclusion, a TaqMan-based fluorescence quantitative PCR method was developed, with the advantages of sensitivity, specificity, and reproducibility. This method can be used for further epidemiological monitoring of PiPV infection.